The Impact of Gadgets on Social-Emotional Development of Early Children During Covid-19 Pandemic - Ridwan Ridwan; Sapriya Utami; Indra Bangsawan (Universitas Negeri Makassar, 2023)
With the Covid-19 crisis, we can see how technology and education have changed. To adapt to these changes, we must accept who we are and continue to acquire new knowledge. Gadgets are often used as a tool that facilitates communication in human life, both in the general and family environments, which also impacts children's social emotionality. This research aims to describe gadgets' impact on early childhood social-emotional development. This study uses a qualitative method. research data obtained through observation and interviews used three stages in analysing the data: reduction, data presentation, and conclusion. The population of this study is 20 parents and three parents with children aged 5-6 years with different professions. Based on the results of the study, it can be concluded that the impact of Gadgets contributes to the formation of children's social and emotional development; the effect of gadgets on the positive side is that children can develop and improve themselves; on the negative side, that occurs in children, namely the loss of awareness of their social life with their environment.